Selenium and Redox Enzyme Activity in Pregnant Women Exposed to Methylmercury - Vasco Branco; Luís Carvalho; Cássia Barboza; Eduarda Mendes; Afonso Cavaco; Cristina Carvalho (MDPI AG, 2022)
Selenium (Se) is a micronutrient with essential physiological functions achieved through the production of selenoproteins. Adequate Se intake has health benefits and reduces mercury (Hg) toxicity, which is important due to its neurotoxicity. This study determined the Se status and redox enzyme, including selenoproteins', activity in pregnant women highly exposed to Hg (between 1 to 54 µg Hg/L blood) via fish consumption. A cross-sectional study enrolling 513 women between the first and third trimester of pregnancy from Madeira, Portugal was conducted, encompassing collection of blood and plasma samples. Samples were analyzed for total Se and Hg levels in whole blood and plasma, and plasma activity of redox-active proteins, such as glutathione peroxidase (GPx), thioredoxin reductase (TrxR) and thioredoxin (Trx). Enzyme activities were related to Se and Hg levels in blood. Se levels in whole blood (65.0 ± 13.1 µg/L) indicated this population had a sub-optimal Se status, which translated to low plasma GPx activity (69.7 ± 28.4 U/L). The activity of TrxR (12.3 ± 5.60 ng/mL) was not affected by the low Se levels. On the other hand, the decrease in Trx activity with an increase in Hg might be a good indicator to prevent fetal susceptibility.